Community collaboration and climate change research in the Canadian Arctic - Pearce, T; Ford, J D; Laidler, G; Smit, B; Duerden, F; Allarut, M; Andrachuk, M; Baryluk, S; Dialla, A; Elee, P; Goose, A; Ikummaq, T; et al. (Polar Research, 2009)
Research on climate change impacts, vulnerability and adaptation, particularly projects aiming to contribute to practical adaptation initiatives, requires active involvement and collaboration with community members and local, regional and national organizations that use this research for policy-making. Arctic communities are already experiencing and adapting to environmental and socio-cultural changes, and researchers have a practical and ethical responsibility to engage with communities that are the focus of the research. This paper draws on the experiences of researchers working with communities across the Canadian Arctic, together with the expertise of Inuit organizations, Northern research institutes and community partners, to outline key considerations for effectively engaging Arctic communities in collaborative research. These considerations include: initiating early and ongoing communication with communities, and regional and national contacts; involving communities in research design and development; facilitating opportunities for local employment; and disseminating research findings. Examples of each consideration are drawn from climate change research conducted with communities in the Canadian Arctic.